Organic-free synthesis of layer-like FAU-type zeolites. Issue 2 (18th November 2014) - Inayat, A.; Schneider, C.; Schwieger, W.
Abstract : The presence of simple inorganic salts during zeolite synthesis turned out to be an effective and easy to handle alternative to organic additives to induce the growth of layer-like zeolite morphologies. Abstract : The formation of layer-like FAU-type zeolites was facilitated in the absence of any organic template. Instead, the addition of simple inorganic salts turned out to be an effective and easy to handle alternative to organic additives to induce morphological and even structural changes during zeolite crystallisation.